SPIRITUAL HIBRIDITY OF NATIVE AMERICAN IN LOUIS EDRICH’S THE ROUND HOUSE: POSTCOLONIAL STUDIES - Achmad Faqih; Muh Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2020)
Louis Edrich is a contemporary Native American writer who writes The Round House. The novel portrays the complexities of individual and cultural identity, focuses on the exigencies of marginalization and cultural survival, which happened to Native Americans, as well as concerns about spirituality and the hybrid form of religion, known as spiritual hybridity. Spiritual hybridity appears to be common practices for Native Americans after the arrival of European and the massive spreading of Christianity. This study is conducted to probe the representation of the spiritual hybridity of Native Americans. The novel is examined using Bhabha’s theory on Hybridity. The dialogue and narration in the form of words, phrases, and sentences in the novel are treated as a data source representing the spiritual hybridity of Native Americans. The analysis results in the representation of the spiritual hybridity of Native Americans,which can be considered as their defense against Christian hegemony. Besides, the representation of spiritual hybridity, as a form of third space, occurs due to a mixture of religious beliefs committed by Native Americans after experiencing religious oppression or discrimination. Spiritual hybridity can be concluded as a new pattern of the struggle and resistance of Native Americans to fight for their tradition. Nowadays, spiritual hybridity for Native American remains a form of resistance towards Christian hegemony.